A taxonomic review of the genus Triscaedecia (Lepidoptera: Alucitidae) in the world fauna - Ustjuzhanin, Petr; Kovtunovich, Vasiliy; Hobern, Donald (Zootaxa, 2019)
The article describes four new species of Alucitidae in the genus Triscaedecia from the Malay and Polynesian regions: Triscaedecia sulawesi Ustjuzhanin, Kovtunovich & Hobern sp. nov., T. sarawaki Ustjuzhanin, Kovtunovich & Hobern sp. nov., T. svetlanae Ustjuzhanin, Kovtunovich & Hobern sp. nov., and T. suva Ustjuzhanin, Kovtunovich & Hobern sp. nov. The female genitalia of Triscaedecia dactyloptera Hampson, 1905 and the adult and the male genitalia of Triscaedecia septemdactyla (Pagenstecher, 1900) are described and illustrated for the first time. Diagnostic characters are specified for each new taxon, genitalia are described and illustrated, and images are provided of adults. A spreadsheet of all known localities and specimens is included as a supplementary file.